The Difference in Mean Blood Pressure Before and After Dark Chocolate Administration in the Elderly - Sabrina Kezia Yohannes; Alfianto Martin (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Hypertension is particularly prevalent among the elderly and requires careful therapy to minimize cardiovascular consequences. Flavanol chemicals found in dark chocolate are thought to enhance endothelial function by increasing the availability of nitric oxide, which may lower blood pressure. This study assessed the acute effect of dark chocolate consumption on systolic and diastolic blood pressure in older persons. A quasi-experimental pre–post design was undertaken among 65 elderly people of Panti Werdha Wisma Mulia and Panti Santa Anna who met the inclusion criteria and given informed consent. A digital sphygmomanometer was used to assess each participant's blood pressure prior to consumption and at 15, 30, and 60 minutes after consuming 30 grammes of 72% dark chocolate. Data normality was assessed using the Kolmogorov–Smirnov test, and paired t-test or Wilcoxon analysis. Systolic blood pressure at 30 minutes (126.14 ± 16.17 mmHg; p = 0.015) and 60 minutes (122.57 ± 16.36 mmHg; p = 0.000) was significantly lower than baseline (130.51 ± 17.54 mmHg). Diastolic blood pressure revealed a significant drop only at 60 minutes (74.26 ± 9.98 mmHg; p = 0.005) from baseline (77.89 ± 14.24 mmHg). Although early post-consumption measures indicated no statistically significant changes, the overall results indicate that dark chocolate produces a considerable short-term hypotensive impact in the elderly. These data imply that dark chocolate may serve as a complementary non-pharmacological strategy to blood pressure management in older populations.